In-situ coherently-composited thermoelectric material, preparation method and application thereof
Patent Information
- Application Number
- CN202111530297.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2021-12-14
- Publication Date
- 2026-10-30
- Estimated Expiration
- 2041-12-14
AI Technical Summary
快离子导体Cu2Se具有高电导率和低热导率,热电性能优异,但是其稳定性差,实际应用较为困难;层状含氧化合物BiCuSeO具有较高的塞贝克系数和较低的热导率,且高温及化学稳定性优异,但是其电导率较低
[0006]本发明旨在至少在一定程度上解决相关技术中的技术问题之一。为此,本发明的一个目的在于提出一种原位共格复合热电材料及其制备方法与应用,该原位共格复合热电材料同时具备优异的热电性能和高稳定性。
Smart Images

Figure CN114203893B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of thermoelectric ceramic materials, specifically relating to an in-situ coherent composite thermoelectric material, its preparation method, and its application. Background Technology
[0002] With the rapid development of the global economy, the shortage of non-renewable resources (such as coal, oil, and natural gas) and the increasing environmental pollution have become problems that humanity must face together. To address this issue, scientists and engineers worldwide are dedicated to developing new clean energy sources and improving existing technologies to enhance energy conversion efficiency. According to incomplete statistics, the vast majority of energy used in industrial production and daily life is not fully utilized, with over 60% of energy consumed as waste heat. Effectively utilizing waste heat can significantly improve energy efficiency. Based on the transport characteristics of microscopic charge carriers and phonons within materials, thermoelectric materials possess the ability to directly convert heat (temperature difference) into electrical energy; moreover, thermoelectric devices are composed of all-solid-state components, offering advantages such as simple construction, safety and reliability, low maintenance costs, and wide application range, making related research areas highly sought after.
[0003] Based on the Seebeck and Peltier effects, thermoelectric devices show promising applications in both thermoelectric power generation and solid-state refrigeration. In power generation, particularly in military and space exploration fields, thermoelectric devices hold an irreplaceable position. For example, radioisotope thermoelectric generators provide power to ensure the normal operation of space probes; thermoelectric power generation from industrial waste heat and automotive exhaust heat is also an important means of improving energy efficiency and the atmospheric environment. In refrigeration, thermoelectric refrigeration devices, due to their advantages such as variable size, no noise, and no need for refrigerants, are widely used in portable refrigerators, portable air conditioners, and chip-based refrigeration.
[0004] The performance of thermoelectric materials is evaluated by the dimensionless thermoelectric figure of merit (ZT), which is expressed as ZT = S 2 σT / κ. Where S is the Seebeck coefficient, σ is the electrical conductivity, κ is the thermal conductivity, and T is the absolute temperature. Therefore, a good thermoelectric material needs to possess a high Seebeck coefficient and electrical conductivity, as well as low thermal conductivity. Fast ion conductor Cu₂Se exhibits high electrical conductivity and low thermal conductivity, resulting in excellent thermoelectric performance, but its poor stability makes practical applications difficult. Layered oxygen-containing compounds BiCuSeO possess a high Seebeck coefficient and low thermal conductivity, along with excellent high-temperature and chemical stability, but its electrical conductivity is relatively low.
[0005] Therefore, existing thermoelectric materials need to be improved. Summary of the Invention
[0006] The present invention aims to solve at least one of the technical problems in the related art to a certain extent. To this end, one objective of the present invention is to provide an in-situ coherent composite thermoelectric material and its preparation method and application. The in-situ coherent composite thermoelectric material has both excellent thermoelectric properties and high stability.
[0007] In one aspect of the present invention, the present invention proposes an in-situ coherent composite thermoelectric material. According to the embodiments of the present invention, the chemical formula of the in-situ coherent composite thermoelectric material is (1-y)Cu 2+x Se-yBi 1-(a+b) Pb a Ca b CuSeO, where 0≤x≤0.02, 0.05≤y≤0.3, 0<a≤0.1, 0<b≤0.1.
[0008] The in-situ coherent composite thermoelectric material according to the embodiments of the present invention has a chemical formula of (1-y)Cu 2+x Se-yBi 1-(a+b) Pb a Ca b CuSeO, in which Cu 2+x Se is Cu2Se with excess Cu of x, Bi 1-(a+b) Pb a Ca b CuSeO is BiCuSeO with Pb and Ca two elements doped at Bi sites in the contents of a and b respectively. By selecting Cu 2+x Se (0≤x≤0.02) and Bi 1-(a+b) Pb a Ca b CuSeO (0<a≤0.1, 0<b≤0.1) to carry out in-situ coherent composite, the two have close carrier concentrations, which is easy to produce an effective composite effect, so that phonons can be effectively scattered, the thermal conductivity can be reduced, and at the same time, the transport of carriers will not be hindered, which is beneficial to the improvement of thermoelectric properties. Meanwhile, in the above composite thermoelectric material, Bi 1-(a+b) Pb a Ca b The mole fraction of CuSeO is 5% to 30%, that is, 0.05≤y≤0.3. The inventors found that if y is less than 0.05, the main phase of the composite sample is Cu2Se with poor stability, and the stability of the obtained sample is poor; while if y is greater than 0.3, the carrier concentration of the obtained composite sample is too high, leading to a decrease in the Seebeck coefficient, an increase in thermal conductivity, and a decline in thermoelectric properties. Therefore, by adopting the Bi 1-(a+b) Pb a Ca bThe in-situ coherent composite thermoelectric material obtained with a higher CuSeO molar fraction exhibits superior high-temperature and chemical stability. In summary, the in-situ coherent composite thermoelectric material of this application possesses both excellent thermoelectric properties and high stability.
[0009] In addition, the in-situ coherent composite thermoelectric material according to the above embodiments of the present invention may also have the following additional technical features:
[0010] In some embodiments of the present invention, 0.01≤x≤0.02, 0.05≤y≤0.25, 0.03≤a≤0.06, and 0.06≤b≤0.1. Therefore, this in-situ coherent composite thermoelectric material possesses both excellent thermoelectric properties and high stability.
[0011] In some embodiments of the present invention, 0.05 ≤ y ≤ 0.2. Therefore, the average thermoelectric figure of merit of this in-situ coherent composite thermoelectric material can exceed 1.0 in the medium-high temperature range (473K-973K), making it suitable for practical applications in waste heat power generation or thermoelectric cooling in the medium-high temperature range, and the material exhibits high stability.
[0012] In some embodiments of the present invention, b = 0.06. Therefore, this in-situ coherent composite thermoelectric material possesses both excellent thermoelectric properties and high stability.
[0013] In a second aspect, the present invention provides a method for preparing the above-mentioned in-situ coherent composite thermoelectric material. According to an embodiment of the present invention, the method includes:
[0014] (1) Mix Bi powder, Bi2O3 powder, Se powder, Cu powder, PbO powder and CaO powder and compress them into tablets to obtain green blanks;
[0015] (2) The green body is heated to induce a self-propagating reaction, thereby obtaining an in-situ coherent composite phase sample;
[0016] (3) The phase sample is ground and then subjected to discharge plasma sintering to obtain an in-situ coherent composite thermoelectric material.
[0017] According to an embodiment of the present invention, the method for preparing the above-mentioned in-situ coherent composite thermoelectric material involves mixing Bi powder, Bi₂O₃ powder, Se powder, Cu powder, PbO powder, and CaO powder, pressing the mixture into a sheet, and then heating the green blank obtained from the pressing to induce a self-propagating reaction, thereby generating (1-y)Cu. 2+x Se-yBi 1-(a+b) Pb a Ca bThe phase-formed sample of CuSeO in-situ coherent composite is a loose bulk, which is relatively difficult for practical application. By grinding the phase-formed sample and then performing spark plasma sintering, a dense in-situ coherent composite thermoelectric material can be obtained. The raw materials used in the method of the present application are existing commercially available elemental substance and oxide raw material powders, which are easily available, and the preparation process is simple, with low requirements for experimental equipment and sites, which is beneficial to large-scale and industrial production. At the same time, the in-situ coherent composite thermoelectric material prepared by the method of the present application has both excellent thermoelectric properties and high stability.
[0018] In addition, the method for preparing the above-mentioned in-situ coherent composite thermoelectric material according to the above embodiments of the present invention may also have the following additional technical features:
[0019] In some embodiments of the present invention, in step (1), the molar ratio of the Bi powder, the Bi2O3 powder, the Se powder, the Cu powder, the PbO powder and the CaO powder is (y(1-a-b) / 3): (y(1-a-b) / 3): 1: (2+x-xy-y): ya: yb, where 0≤x≤0.02, 0.05≤y≤0.3, 0<a≤0.1, 0<b≤0.1. As a result, the obtained in-situ coherent composite thermoelectric material has both excellent thermoelectric properties and high stability.
[0020] In some embodiments of the present invention, in step (1), the pressure for tableting is 3 to 6 MPa. This can make the contact between the powders more sufficient, thereby facilitating the occurrence of the self-propagating reaction.
[0021] In some embodiments of the present invention, in step (2), the heating temperature is 400 to 600 degrees Celsius, and the time is 1 to 2 minutes. This is beneficial to causing the green body to undergo a self-propagating reaction.
[0022] In some embodiments of the present invention, in step (3), the sintering temperature is 873 to 973 K, the sintering pressure is 40 to 50 MPa, and the holding time is 3 to 5 minutes. This is beneficial to obtaining a dense in-situ coherent composite thermoelectric material.
[0023] In a third aspect of the present invention, the present invention provides a thermoelectric device. According to an embodiment of the present invention, the thermoelectric device includes the above-mentioned in-situ coherent composite thermoelectric material or the in-situ coherent composite thermoelectric material obtained by the above-mentioned method. As a result, the thermoelectric device has excellent thermoelectric properties and a long service life, and has good application prospects in both temperature difference power generation and solid-state refrigeration.
[0024] The additional aspects and advantages of the present invention will be partly given in the following description, and partly will become apparent from the following description, or be understood through the practice of the present invention. Brief Description of the Drawings
[0025] The above and / or additional aspects and advantages of the present invention will become apparent and readily understood from the description of the embodiments taken in conjunction with the following drawings, in which:
[0026] Figure 1 This is a schematic flowchart of a method for preparing the above-mentioned in-situ coherent composite thermoelectric material according to an embodiment of the present invention;
[0027] Figure 2 This is the XRD pattern of the product obtained in Example 1;
[0028] Figure 3 This is the XRD pattern of the product obtained in Example 2;
[0029] Figure 4 This is a cross-sectional SEM backscattering image of the product prepared in Example 3;
[0030] Figure 5 It is the average ZT value of the product prepared in Example 4. Detailed Implementation
[0031] The embodiments described below with reference to the accompanying drawings are exemplary and intended to explain the invention, and should not be construed as limiting the invention.
[0032] In a first aspect, the present invention provides an in-situ coherent composite thermoelectric material. According to an embodiment of the present invention, the chemical formula of the above-mentioned in-situ coherent composite thermoelectric material is (1-y)Cu. 2+x Se-yBi 1-(a+b) Pb a Ca b CuSeO, where 0≤x≤0.02, 0.05≤y≤0.3, 0 <a≤0.1,0<b≤0.1。
[0033] The inventors discovered that its chemical formula is (1-y)Cu 2+x Se-yBi 1-(a+b) Pb a Ca b CuSeO, where Cu 2+x Se is Cu₂Se with excess Cu x, Bi 1-(a+b) Pb a Ca b CuSeO is a BiCuSeO doped with Pb and Ca at Bi sites with a and b contents, respectively. This is achieved by selecting Cu... 2+x Se(0≤x≤0.02) and Bi 1-(a+b) Pb a Ca bCuSeO (0<a≤0.1, 0<b≤0.1) for in-situ coherent recombination. The two have close carrier concentrations, which easily produce an effective recombination effect, thereby effectively scattering phonons, reducing thermal conductivity, while not hindering carrier transport, and facilitating the improvement of thermoelectric properties. Meanwhile, in the above in-situ coherent composite thermoelectric material, Bi 1-(a+b) Pb a Ca b The molar fraction of CuSeO is 5% to 30%, that is, 0.05≤y≤0.3. The inventors have found that if y is less than 0.05, the main phase of the composite sample is Cu₂Se with poor stability, and the obtained sample has poor stability; and if y is greater than 0.3, the carrier concentration of the obtained composite sample is too high, leading to a decrease in Seebeck coefficient, an increase in thermal conductivity, and a decline in thermoelectric properties. Therefore, by using the Bi of the present application 1-(a+b) Pb a Ca b The molar fraction of CuSeO, the obtained in-situ coherent composite thermoelectric material has superior high temperature and chemical stability. In summary, the in-situ coherent composite thermoelectric material of the present application has both excellent thermoelectric properties and high stability.
[0034] Further, the above in-situ coherent composite thermoelectric material (1-y)Cu 2+x Se-yBi 1-(a+b) Pb a Ca b In CuSeO, 0.01≤x≤0.02, 0.05≤y≤0.25, 0.03≤a≤0.06, 0.06≤b≤0.1. Thereby, the comprehensive performance of the in-situ coherent composite thermoelectric material can be further improved.
[0035] Further, the above in-situ coherent composite thermoelectric material (1-y)Cu 2+x Se-yBi 1-(a+b) Pb a Ca b In CuSeO, 0.05≤y≤0.2. As a result, the average thermoelectric figure of merit of this in-situ coherent composite thermoelectric material can exceed 1.0 in the medium-high temperature region (473K-973K), which is suitable for practical applications of waste heat power generation or thermoelectric refrigeration in the medium-high temperature region, and the material has high stability.
[0036] Further, the above in-situ coherent composite thermoelectric material (1-y)Cu 2+x Se-yBi 1-(a+b) Pb a Ca b In CuSeO, b=0.06. Thereby, Cu 2+x Se and Bi 1-(a+b) Pb a Ca bCuSeO can achieve the optimal composite effect, and the material has high stability.
[0037] In a second aspect of the present invention, the present invention provides a method for preparing the above in-situ coherent composite thermoelectric material. According to an embodiment of the present invention, reference is made to Figure 1 , the method comprises:
[0038] S100: mixing Bi powder, Bi2O3 powder, Se powder, Cu powder, PbO powder and CaO powder, followed by tableting
[0039] In this step, a green body can be obtained by mixing Bi powder, Bi2O3 powder, Se powder, Cu powder, PbO powder and CaO powder and then performing tableting. The inventor has found that tableting the raw material powders into a block can make the contact between the powders more sufficient, thereby facilitating the occurrence of the subsequent self-propagating reaction. Preferably, before tableting the composite powder obtained by mixing Bi powder, Bi2O3 powder, Se powder, Cu powder, PbO powder and CaO powder, the composite powder is ground in an agate mortar for 15 to 25 min, preferably 20 min. Thereby, all the raw material powders can be fully and uniformly mixed. Specifically, the above tableting process is carried out in a tablet press, and all the raw material powders are commercially available elemental powders or oxide powders with a purity of more than 99.5%. Further, the pressure for the above tableting is 3 to 6 MPa. The inventor has found that if the tableting pressure is too low, the formed block is not compact enough, and the subsequent heating reaction is insufficient; while if the tableting pressure is too high, the block is prone to fracture during demolding. Therefore, the tableting pressure adopted in the present application is beneficial to the sufficient proceeding of the subsequent self-propagating reaction and facilitates demolding.
[0040] Further, the molar ratio of the Bi powder, Bi2O3 powder, Se powder, Cu powder, PbO powder and CaO powder is (y(1-a-b) / 3):(y(1-a-b) / 3):1:(2+x-xy-y):ya:yb, where 0≤x≤0.02, 0.05≤y≤0.3, 0<a≤0.1, 0<b≤0.1. The inventor has found that if the x value is too large, the carrier concentration of the obtained composite sample is too low, and the electrical conductivity decreases; meanwhile, if the y value is too small, the main phase of the composite sample is Cu2Se with poor stability, and the obtained sample has poor stability; while if the y value is too large, the carrier concentration of the obtained composite sample is too high, resulting in a decrease in the Seebeck coefficient, an increase in thermal conductivity, and a decline in thermoelectric performance. In addition, if the a value is too large, the carrier concentration of the obtained composite sample is too high, resulting in a decrease in the Seebeck coefficient, an increase in thermal conductivity, and a decline in thermoelectric performance; and if the b value is too large, a precipitated phase is easily formed, which affects the stability. Therefore, by adopting the molar ratio of the present application, the prepared in-situ coherent composite thermoelectric material has both excellent thermoelectric performance and high stability.
[0041] S200: heating the green body
[0042] In this step, the green blank obtained in step S100 is heated for a certain period of time, after which a self-propagating reaction occurs. Heating is then stopped, and the blank is allowed to cool naturally to obtain (1-y)Cu. 2+x Se-yBi 1-(a+b) Pb a Ca b The phase-forming sample is a CuSeO in-situ coherent composite. It should be noted that the specific heating method described above is not particularly limited, and those skilled in the art can choose according to actual needs; for example, heating can be performed using the outer flame of an alcohol lamp.
[0043] Furthermore, the heating temperature is 400–600 degrees Celsius, and the time is 1–2 minutes. The inventors discovered that if the heating temperature is too low, the self-propagating reaction cannot be initiated; while if the heating temperature is too high, Bi and Se elements easily volatilize. Simultaneously, if the heating time is too short, the self-propagating reaction cannot be initiated; while if the heating time is too long, Bi and Se elements easily volatilize and are lost into the air. Therefore, the heating conditions described in this application are beneficial for initiating the self-propagating reaction while avoiding element loss.
[0044] S300: The phase-forming sample is ground and then subjected to spark plasma sintering.
[0045] In this step, an in-situ coherent composite thermoelectric material is obtained by grinding the phase-formed sample and then performing spark plasma sintering. The inventors discovered that the phase-formed sample obtained in step S200 is a loose, bulk material, which is difficult to apply in practice. By grinding the phase-formed sample and then performing spark plasma sintering, a dense, in-situ coherent composite thermoelectric material can be obtained, which is beneficial for practical applications. Specifically, the above-mentioned spark plasma sintering process is carried out in a spark plasma sintering furnace.
[0046] Furthermore, the sintering temperature is 873–973 K, the sintering pressure is 40–50 MPa, and the holding time is 3–5 min. The inventors have discovered that if the sintering temperature is too low, the sample will not be dense; while if the sintering temperature is too high, the sample will easily melt. Similarly, if the sintering pressure is too low, the sample will not be dense; while if the sintering pressure is too high, the sample will be brittle. Additionally, if the holding time is too short, the sample will not be dense; while if the holding time is too long, the grains will grow, affecting the thermoelectric properties. Therefore, the sintering conditions described in this application are beneficial for obtaining composite materials with high density and excellent thermoelectric properties.
[0047] The inventors discovered that by mixing Bi powder, Bi₂O₃ powder, Se powder, Cu powder, PbO powder, and CaO powder, compressing the mixture into tablets, and then heating the resulting green tablets to induce a self-propagating reaction, (1-y)Cu can be generated. 2+x Se-yBi 1-(a+b) Pb a Ca bThe CuSeO in-situ coherent composite phase sample, being a loose bulk, is difficult to apply in practice. By grinding the phase sample and then performing spark plasma sintering, a dense in-situ coherent composite thermoelectric material can be obtained. The method in this application uses readily available commercially available elemental and oxide powders, which are readily available, and the preparation process is simple, requiring minimal experimental equipment and facilities, thus facilitating large-scale industrial production. Furthermore, the in-situ coherent composite thermoelectric material prepared using this method possesses both excellent thermoelectric properties and high stability.
[0048] In a third aspect, the present invention provides a thermoelectric device. According to embodiments of the present invention, the thermoelectric device comprises the aforementioned in-situ coherent composite thermoelectric material or an in-situ coherent composite thermoelectric material obtained by the aforementioned method. Therefore, the thermoelectric device possesses excellent thermoelectric performance and a long service life, showing promising application prospects in both thermoelectric power generation and solid-state refrigeration. It should be noted that the features and advantages described above for the in-situ coherent composite thermoelectric material and the method for preparing the aforementioned in-situ coherent composite thermoelectric material also apply to this thermoelectric device, and will not be repeated here.
[0049] The embodiments of the present invention are described in detail below. It should be noted that the embodiments described below are exemplary and are only used to explain the present invention, and should not be construed as limiting the present invention. In addition, unless otherwise specified, all reagents used in the following embodiments are commercially available or can be synthesized according to the methods described herein or known to others. For reaction conditions not listed, they are also readily available to those skilled in the art.
[0050] Example 1
[0051] (1) Using Bi powder, Bi2O3 powder, Se powder, Cu powder, PbO powder and CaO powder as raw materials, weigh 12g of raw material powder according to the molar ratio of (1 / 3y(1-ab)):(1 / 3y(1-ab)):1:(2+x-xy-y):ya:yb (where x=0; y=30%; a=3%; b=6%).
[0052] (2) Grind in an agate mortar for 20 minutes. After mixing evenly, take out the composite powder and place it in a metal mold (12.5 mm in diameter) to compress it in a tablet press at a pressure of 5 MPa. Place the compacted block in an alumina crucible and heat it in the outer flame of an alcohol lamp (temperature 600℃). After about 30 seconds, a self-propagating reaction will occur. Remove the alcohol lamp and wait for it to cool naturally.
[0053] (3) The cooled loose block was ground until it was uniform and free of large particles. It was then placed in a graphite mold and subjected to discharge plasma sintering at a temperature of 923 K and a pressure of 40 MPa for 3 min to obtain the in-situ coherent composite thermoelectric material 0.7Cu2Se-0.3Bi. 0.91 Pb 0.03 Ca 0.06 CuSeO.
[0054] The in-situ coherent composite thermoelectric material prepared in Example 1 was characterized by XRD, and its XRD pattern is referenced. Figure 2 The main phases were found to be Cu2Se and BiCuSeO. The obtained sample exhibited a conductivity of 316 S / cm, a Seebeck coefficient of 197 μV / K, and a ZT value exceeding 1.5 at 700℃. The sample showed no significant change after three cycles from room temperature to 700℃, demonstrating excellent stability.
[0055] Example 2
[0056] (1) Using Bi powder, Bi2O3 powder, Se powder, Cu powder, PbO powder and CaO powder as raw materials, weigh 12g of raw material powder according to the molar ratio of (1 / 3y(1-ab)):(1 / 3y(1-ab)):1:(2+x-xy-y):ya:yb (where x=1%; y=10%; a=6%; b=6%).
[0057] (2) Grind in an agate mortar for 20 minutes. After mixing evenly, take out the composite powder and place it in a metal mold (12.5 mm in diameter) to compress it in a tablet press at a pressure of 5 MPa. Place the compacted block in an alumina crucible and heat it in the outer flame of an alcohol lamp (temperature 600℃). After about 30 seconds, a self-propagating reaction will occur. Remove the alcohol lamp and wait for it to cool naturally.
[0058] (3) The cooled loose block was ground until uniform and free of large particles, placed in a graphite mold, and subjected to discharge plasma sintering at a temperature of 973 K and a pressure of 50 MPa for 4 min to obtain the in-situ coherent composite thermoelectric material 0.9Cu. 2.01 Se-0.1Bi 0.88 Pb 0.06 Ca 0.06 CuSeO.
[0059] The in-situ coherent composite thermoelectric material prepared in Example 2 was characterized by XRD, and its XRD pattern is referenced. Figure 3The main phases were found to be Cu2Se and BiCuSeO. The obtained sample exhibited a conductivity of 253 S / cm, a Seebeck coefficient of 227 μV / K, and a ZT value exceeding 2.0 at 700℃. After three cycles from room temperature to 700℃, the sample showed no significant changes, demonstrating excellent stability.
[0060] Example 3
[0061] (1) Using Bi powder, Bi2O3 powder, Se powder, Cu powder, PbO powder and CaO powder as raw materials, weigh 12g of raw material powder according to the molar ratio of (1 / 3y(1-ab)):(1 / 3y(1-ab)):1:(2+x-xy-y):ya:yb (where x=2%; y=25%; a=6%; b=6%).
[0062] (2) Grind in an agate mortar for 20 minutes. After mixing evenly, take out the composite powder and place it in a metal mold (12.5 mm in diameter) to compress it in a tablet press at a pressure of 5 MPa. Place the compacted block in an alumina crucible and heat it in the outer flame of an alcohol lamp (temperature 600℃). After about 30 seconds, a self-propagating reaction will occur. Remove the alcohol lamp and wait for it to cool naturally.
[0063] (3) The cooled loose block was ground until uniform and free of large particles, placed in a graphite mold, and subjected to discharge plasma sintering at a temperature of 973 K and a pressure of 40 MPa for 3 min to obtain the in-situ coherent composite thermoelectric material 0.75Cu. 2.02 Se-0.25Bi 0.88 Pb 0.06 Ca 0.06 CuSeO.
[0064] The cross-section of the in-situ coherent composite thermoelectric material prepared in Example 3 was observed using a scanning electron microscope in backscattered electron mode. The SEM image is shown in the reference image. Figure 4 The bright areas in the image are Bi. 0.88 Pb 0.06 Ca 0.06 CuSeO, the dark gray part is Cu. 2.02 The obtained sample exhibits a conductivity of 275 S / cm, a Seebeck coefficient of 210 μV / K, and a ZT value exceeding 1.8 at 700℃. The sample shows no significant change after three cycles from room temperature to 700℃, demonstrating excellent stability.
[0065] Example 4
[0066] (1) Using Bi powder, Bi2O3 powder, Se powder, Cu powder, PbO powder and CaO powder as raw materials, the raw material powders were weighed according to the molar ratio of (1 / 3y(1-ab)):(1 / 3y(1-ab)):1:(2+x-xy-y):ya:yb (where x=2%; y=5%, 10%, 15%, 20%; a=6%; b=6%), a total of 4 portions, each 12g, and the samples were recorded as α, β, γ and δ;
[0067] (2) Grind in an agate mortar for 20 minutes. After mixing evenly, take out the composite powder and place it in a metal mold (12.5 mm in diameter) to compress it in a tablet press at a pressure of 5 MPa. Place the compacted block in an alumina crucible and heat it in the outer flame of an alcohol lamp (temperature 600℃). After about 30 seconds, a self-propagating reaction will occur. Remove the alcohol lamp and wait for it to cool naturally.
[0068] (3) The cooled loose block was ground until uniform and free of large particles, placed in a graphite mold, and subjected to discharge plasma sintering at a temperature of 973 K and a pressure of 40 MPa for 3 min to obtain the composite thermoelectric material 0.95Cu. 2.02 Se-0.05Bi 0.88 Pb 0.06 Ca 0.06 CuSeO (α sample), 0.9Cu 2.02 Se-0.1Bi 0.88 Pb 0.06 Ca 0.06 CuSeO (β sample), 0.85Cu 2.02 Se-0.15Bi 0.88 Pb 0.06 Ca 0.06 CuSeO (γ sample), 0.8Cu 2.02 Se-0.2Bi 0.88 Pb 0.06 Ca 0.06 CuSeO (δ sample).
[0069] Thermoelectric properties of the four samples prepared in Example 4 were tested, and the ZT values of the α, β, γ, and δ samples at 700℃ were all above 2.0. Simultaneously, the average ZT value of the four samples in the temperature range of 473K to 973K was calculated. (Reference) Figure 5 The average ZT values of all four samples exceeded 1.2, with the α sample having an average ZT value of approximately 1.7. All samples showed no significant changes after three cycles of cycling from room temperature to 700℃, demonstrating excellent stability. This indicates that the in-situ coherent selenium oxide prepared using this method and with this composition possesses excellent thermoelectric properties in the mid-to-high temperature range, showing potential for waste heat power generation or thermoelectric cooling applications within this temperature range.
[0070] Comparative Example
[0071] The difference from Example 4 is that in step (1), Bi powder, Bi2O3 powder, Se powder and Cu powder are used as raw materials, and the raw material powders are weighed according to the molar ratio of 1 / 3y:1 / 3y:1:(2-y) (where y = 1%), and the rest is the same as in Example 4. Finally, the thermoelectric material 0.09Cu2Se-0.01BiCuSeO is obtained, with a room temperature conductivity of 342 S / cm, a room temperature Seebeck coefficient of 148 μV / K, and a ZT value of less than 1.0 at 700℃. Its thermoelectric performance is significantly lower than that of the sample in Example 4; and it has slight deformation after three cycles from room temperature to 700℃, indicating poor stability.
[0072] In the description of this specification, the references to terms such as "one embodiment," "some embodiments," "example," "specific example," or "some examples," etc., indicate that a specific feature, structure, material, or characteristic described in connection with that embodiment or example is included in at least one embodiment or example of the present invention. In this specification, the illustrative expressions of the above terms do not necessarily refer to the same embodiment or example. Furthermore, the specific features, structures, materials, or characteristics described may be combined in any suitable manner in one or more embodiments or examples. Moreover, without contradiction, those skilled in the art can combine and integrate the different embodiments or examples described in this specification, as well as the features of different embodiments or examples.
[0073] Although embodiments of the present invention have been shown and described above, it is understood that the above embodiments are exemplary and should not be construed as limiting the present invention. Those skilled in the art can make changes, modifications, substitutions and variations to the above embodiments within the scope of the present invention.
Claims
1. A method for preparing in-situ coherent composite thermoelectric materials, characterized in that, include: (1) Mix Bi powder, Bi2O3 powder, Se powder, Cu powder, PbO powder and CaO powder and compress them into tablets to obtain green blanks; (2) The green body is heated to induce a self-propagating reaction, thereby obtaining an in-situ coherent composite phase sample; (3) The phase-forming sample is ground and then subjected to spark plasma sintering to obtain an in-situ coherent composite thermoelectric material. The molar ratio of Bi powder, Bi₂O₃ powder, Se powder, Cu powder, PbO powder, and CaO powder is (y(1-ab) / 3):(y(1-ab) / 3):1:(2+x-xy-y):ya:yb, where 0 x 0.02, 0.05 y 0.3, 0 0.1, 0 0.1, In step (1), the pressure of the tablet is 3MPa~6MPa. In step (2), the heating temperature is 400~600 degrees Celsius, and the time is 1~2 minutes. In step (3), the sintering temperature is 873~973K, the sintering pressure is 40~50MPa, and the holding time is 3~5min.
2. The method according to claim 1, characterized in that, 0.01 x 0.02,0.05 y 0.25,0.03 a 0.06,0.06 b 0.1。 3. The method according to claim 2, characterized in that, 0.05 y 0.2。 4. The method according to any one of claims 1 to 3, characterized in that, b=0.06。 5. An in-situ coherent composite thermoelectric material, characterized in that, The in-situ coherent composite thermoelectric material is prepared by any one of claims 1 to 4.
6. A thermoelectric device, characterized in that, The thermoelectric device includes the in-situ coherent composite thermoelectric material as described in claim 5 or the in-situ coherent composite thermoelectric material obtained by the method described in any one of claims 1 to 4.
Citation Information
Patent Citations
Method of preparing homogeneous block thermoelectric material through one-step in situ reaction
CN105990511A
Ultra-rapid preparation method for Cu2Se / BiCuSeO bulk composite thermoelectric material
CN107793154A
